Recent social experience alters song behavior in Drosophila. - Roemschied, F.A.; Ireland, E.C.; Calhoun, A.J.; Choi, M.; Ahmed, O.M.; Murthy, M. (Current Biology, 2026)
Acoustic communication is widespread among animals, but only a small number of species develop their communication signals through learning.[1] In most species, the production of acoustic signals is thought to be hard-wired. Male Drosophila melanogaster are born knowing how to perform their courtship songs,[2][,][3] which comprise alternations of three syllable types (two "pulse" modes and one "sine" mode[4]). Although males do not learn their songs, their singing is highly flexible[5]: males adjust both pattern and amplitude relative to female feedback[6][,][7] and internal state.[8] We therefore asked whether males can change the mapping between social context and song production-a form of "usage learning" involving alteration of the context in which an innate signal is used.[9][,][10] Social experience-dependent learning in male Drosophila has been studied mainly as associative suppression of courtship,[11][,][12][,][13] leaving open whether males can adjust their courtship strategy. Such usage learning could optimize innate behaviors for novel circumstances and has been described in other animals.[14][,][15][,][16] Here, we use closed-loop optogenetics to perturb female feedback and demonstrate that Drosophila melanogaster males that experience such perturbed feedback subsequently alter the context in which they sing with new females, enabling the dissection of the genetic, neural circuit, and evolutionary mechanisms of usage learning.